The parent factor in Toddlers’ self-regulation: parental co-regulation, beliefs, and the effectiveness of a parent training - Erdmann, Kim (2019)
Self-regulation is one of the hallmarks in early childhood and develops in direct social interaction between the child and the caregiver (Kopp, 1982). Toddlerhood demarcates the beginning of a period of rapid growth in child self-regulation (Garon, Bryson, & Smith, 2008). This dissertation focuses on the parent factor in toddlers’ self-regulation and addresses three major questions. First, how do parents’ co-regulation behaviour and self-efficacy beliefs relate to toddlers’ self-regulation and problem-solving performance? Second, which factors may affect parents’ co-regulation behaviour in toddlerhood? And third, how may parental co-regulation behaviours and associated beliefs be promoted at an early stage? To address these questions, a quasi-experimental intervention study has been conducted, including parents of full-term and preterm born two-year old toddlers, and has resulted in three empirical papers that are presented in this dissertation. Concerning the first question, Paper 1 provides evidence for direct (but no indirect) effects from parents’ negative co-regulation practices and domain-specific self-efficacy beliefs to toddlers’ inhibitory control (parent-report) six weeks later. Complementing these findings, the second paper analyses the contribution of parents’ cold co-regulation behaviour (scaffolding) to the parent-child problem-solving performance. Different levels of parental scaffolding are assessed (use of scaffolding means, scaffolding intentions, and process variables) that significantly and differentially relate to the parent-child problem-solving performance. With respect to the second question, Paper 2 also examines determinants of parental scaffolding, precisely how parent (parenting stress), child (preterm birth, cognitive development), and context factors (socioeconomic status, the type of problem-solving task) relate to parents’ scaffolding behaviour. The findings suggest that parental scaffolding differs depending on child cognitive development and the task at hand, but not child birth status, parenting stress, or family socioeconomic status. Finally, and regarding the third question, in Paper 3 evidence is provided that a training of parental co-regulation (especially the combination of scaffolding and sensitivity) may enhance parents’ beliefs about co-regulation and the promotion of learning the most, both in parents of full- and preterm born toddlers. Taken together, this dissertation complements previous research on the parent factor in the development of self-regulation in early childhood. The results underline the importance of taking into account the mental level of the caregiver, meaning self-efficacy beliefs, as well as child and context factors when analysing this interplay. The findings are discussed in light of the existing evidence and prevailing theories, and provide an outlook for further directions. The thesis also offers critical implications for the preventive work and clinical practice.